2020
DOI: 10.3389/fmicb.2020.539604
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Fatty Acids Degradation by Desulfomonile Species and Proposal of “Candidatus Desulfomonile Palmitatoxidans”

Abstract: Microbial communities with the ability to convert long-chain fatty acids (LCFA) coupled to sulfate reduction can be important in the removal of these compounds from wastewater. In this work, an enrichment culture, able to oxidize the long-chain fatty acid palmitate (C16:0) coupled to sulfate reduction, was obtained from anaerobic granular sludge. Microscopic analysis of this culture, designated HP culture, revealed that it was mainly composed of one morphotype with a typical collar-like cell wall invagination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Within the δ-proteobacteria nodes of Module I, the Haliangium (Fudou et al, 2002 ) genus was halophilic while Gobacter (Coates et al, 2001 ) genus could oxidize volatile fatty acids and some aromatic compounds using Fe(III) as electron acceptors. Syntrophobacter (Chen et al, 2005 ) genus within the δ-proteobacteria nodes was reported to degrade propionate in syntrophic association with methanogens, and Desulfomonile (Alves et al, 2020 ) genus could degrade long-chain fatty acids using sulfate as electron acceptors. In addition, Methylobacter (Wartiainen et al, 2006 ) genus within the γ-proteobacteria nodes was a methane-oxidizing bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…Within the δ-proteobacteria nodes of Module I, the Haliangium (Fudou et al, 2002 ) genus was halophilic while Gobacter (Coates et al, 2001 ) genus could oxidize volatile fatty acids and some aromatic compounds using Fe(III) as electron acceptors. Syntrophobacter (Chen et al, 2005 ) genus within the δ-proteobacteria nodes was reported to degrade propionate in syntrophic association with methanogens, and Desulfomonile (Alves et al, 2020 ) genus could degrade long-chain fatty acids using sulfate as electron acceptors. In addition, Methylobacter (Wartiainen et al, 2006 ) genus within the γ-proteobacteria nodes was a methane-oxidizing bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…Desulfobacter postgatei (Bin 481), a sulphate reducing bacteria in NCBI had fadL gene but no lipase gene. We do not know whether or not this bacterium is a cheater, but uptake of long-chain fatty acids and improved lipid degradation have been confirmed for other sulphate reducers (Alves et al, 2020;Florentino et al, 2020).…”
Section: Which Are the Lipolytic Mags And Why They Have Lipases?mentioning
confidence: 93%
“…Glycerol, ethanol, butanol, 1,3-PDO and 1,2-PDO were analyzed by HPLC using a Varian Aminex 87H (300 × 7.8 mm) column with a mobile phase of 5 mmol L −1 H 2 SO 4 at a flow rate of 0.7 mL min −1 , with the column temperature set at 60 °C and refractive index (RI) detection. Total dissolved sulfide was measured using cuvette tests and a DR 2800 spectrophotometer (Hach-Lange GmbH, Düsseldorf, Germany), as described by Alves et al ( 2020 ). Total sulfide species were calculated from the measured dissolved sulfide values, considering the dissociation constants of the acid and pH = 7.5.…”
Section: Methodsmentioning
confidence: 99%